Pengaruh Akupresur Lo4 (he kuk) dan Thai Cong terhadap Tingkat Nyeri Persalinan Kala I pada Ibu Bersalin - Anita Anita (Jurnal Kesehatan, 2018)
The study of women in the first stage of labor using McGill Pain Questionnaire to assess pain found that 60% of maternity described pain due to uterine contractions was very severe (intolerable, unverable, extremely severe), 30% moderate pain. In multipara 45% of pain is severe, 30% is moderate pain, 25% is mild pain (Acute Pain Services (APS), 2007). The aim of this study was to determine the effect of acupressure on the level of labor pain at the first time in maternity. Type of quantitative research, research design Quasy experiment. The population of first-time maternity with a 4-6 cm opening numbered 45 women giving birth per month, a sample of 40 respondents. The one group pre - post-test research design with interventions with acupressure point combinations L04 (he kuk) and thai cong that were carried out during the first active phase was 4-6 for 40 times at the time of his joke. The results showed that the level of first stage pain in maternity before acupressure was 6.00, SD 1,219 and after acupressure was 5.05 SD 1,218, it was concluded that there was an acupressure effect on the level of labor pain (p-value=0,000). The application of L04 (he kuk) acupressure and Cong Thai can reduce labor pain in the first stage active phase of opening 4-6.